Development and hygroscopic behavior of freeze-dried cavendish bananas - Vargas, Gladys Michelle Noveno
ABSTRACT Cavendish bananas were utilized in the development of a non-sulfited dehydrated product. Freeze drying method of dehydration was used to obtain a dehydrated product of the best quality. In this study, the effectivity of pineapple juice, citric acid and sodium metabisulfite in inhibiting enzymatic browning was considered. The moisture sorption isotherm and monolayer value of freeze-dried bananas were established. Phase I determined the best anti-browning substitute for sodium metabisulfite. Sensory evaluation of the final products revealed that the samples treated with sodium metabisulfite, citric acid, and pineapple juice do not differ significantly in terms of odor, flavor, texture and over-all acceptability. However, the three treated products were found to be significantly different in terms of color. Sodium metabisulfite was found to be the best anti-browning agent. Pineapple juice and citric acid may used to repalce sodium metabisulfite when its use should be avoided. In Phase II, the moisture sorption isotherm of the product was established and its monolayer value calculated. From its sorption isotherm, freeze-dried bananas were found to be hygroscopic and needs impermeable packaging. Its monolayer value was computed as 9.12 and it needs to be kept in a place with 17% relative humidity to maintain its food stability.